The Influence of Employee Engagement and Intrinsic Motivation On Performance Through Organizational Learning As an Intervening Variable - Ryan Ardana Putra; Hega Anindita Medissiana (Universitas 17 Agustus 1945 Semarang, 2026)
This study aims to examine the influence of employee engagement and intrinsic motivation on employee performance, and examine employee engagement and intrinsic motivation on organizational learning, as well as examine employee engagement and intrinsic motivation on employee performance through organizational learning. The population used in this study was 84 employees of the Department of Industry, Trade, Cooperatives, and Micro, Small, and Medium Enterprises (MSMEs) of Pekalongan Regency.The data analysis techniques used in this study were descriptive and inferential analysis. Seven hypotheses were tested using Structural Equation Modeling Partial Least Squares (PLS).The results of the study showthere is a positive and significant influenceemployee engagementon employee performance, intrinsic motivation has a positive and significant effect on employee performance, employee engagementpositive and significant influenceon organizational learning, intrinsic motivation has a positive and significant effect on organizational learning, employee engagement has a positive and significant effect on employee performance through organizational learning, intrinsic motivation has a positive and significant effect on employee performance through organizational learning.